TEMPERATURE CALCULATIONS IN FRICTION STIR WELDING WITH ALUMINIUM ALLOYS - Roman R. Kotlyshev; Konstantin G. Shuchev; Alexander V. Kramskoy (Advanced Engineering Research)
Energy heat balance is calculated, and an analytical model of temperature calculations in friction stir welding is offered. Calculations show that the surface temperature makes 440 °С, and the temperature at depth of 2 mm from the surface makes 480 °С.